Vestibulocochlear symptoms as the first manifestation of acquired syphilis: Report of two cases - Cerqueira Rezende, Natália (2021)
Report of 2 cases of acquired syphilis in two male patients, which presented vestibulocochlear symptoms with bilateral hearing loss and dizziness, besides other cranial nerves disorders, as described in first case. Both patients presented positive outcome, with improvement of symptoms after treatment. It is highlighted the importance of diagnostic suspicion for the disease, once it can be cured and prevented.